Exploring the pharmacological mechanisms of Shuanghuanglian against T-cell acute lymphoblastic leukaemia through network pharmacology combined with molecular docking and experimental validation. (31st December 2023) - Yang, You; Yang, Yan; Shen, Yunfu; Liu, Jing; Zeng, Yan; Wei, Chengming; Liu, Chunyan; Pan, Yansha; Guo, Qulian; Zhong, Fangfang; Guo, Ling; Liu, Wenjun
Abstract: Context: Due to the poor prognosis of T-cell acute lymphoblastic leukaemia (T-ALL), there is an urgent need to identify safer and more cost-effective drugs. Objective: This study evaluated the antitumour activity of Shuanghuanglian (SHL) on T-ALL cells and elucidated the mechanism. Materials and methods: Jurkat and Molt4 cells were treated with SHL (0.1, 0.2 and 0.4 mg/mL) for 24 and 48 h. The controls were treated with RPMI 1640 containing 10% foetal bovine serum. Cell viability was evaluated through Cell Counting Kit-8 assay. Patterns of death and signalling pathway alterations caused by SHL were identified by network pharmacology combined with GO enrichment analysis and then were verified by Hoechst 33342 staining, Annexin V-FITC/PI staining and Western blotting. Interactions of the active ingredients with targets were analysed by molecular docking. Results: The IC50 values of SHL in Jurkat and Molt4 cells were 0.30 ± 0.10 and 0.48 ± 0.07 mg/mL, respectively, at 24 h and 0.27 ± 0.05 and 0.30 ± 0.03 mg/mL at 48 h. In T-ALL, 117 target genes of SHL were mainly enriched in the apoptosis and NOTCH signalling pathways. SHL induced apoptosis was confirmed by Hoechst 33342 staining and flow cytometry. The protein levels of cleaved caspase-7 and cleaved PARP were significantly increased but those of cleaved NOTCH1 and MYC were reduced. The active ingredients of SHL can interact with γ-secretase. Discussion and conclusions: SHL induces apoptosis in T-ALL cells via the NOTCH1-MYC pathway and may be a potential drug for the treatment of T-ALL.